Synthesis by the polymeric precursor method and characterization of undoped and Sn, Cr and V-doped ZrTiO4 - de Lucena, P. R.; Pessoa-Netob, O. D.; dos Santos, IMG; Souza, A. G.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2005)
In this work, zirconium titanate doped with 0. 1, 0.2, and 0.4 mole% of tin, chromium and vanadium was synthesized by the polymeric precursors method and characterized by thermal analysis (TG/DTA), X-ray diffraction (XRD), nitrogen adsorption and scanning electronic microscopy (SEM). The powder presented two mass losses attributed to the exit of water and to the pyrolysis of the organic material. The surface area reduction observed from 500 degrees C indicates the beginning of the sintering process. All the dopants led to changes in the lattice parameters and to the decrease of both crystallite size and particle size. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ZrTiO4; crystallization; doping; polymeric precursor method; nuclei grow